Feasibility of an iterative rehabilitation intervention for stroke delivered remotely using mobile health technology - Kringle, Emily A. (Disabil Rehabil Assist Technol, 2019)
BACKGROUND: Telehealth affords rehabilitation professionals opportunities to expand access to intervention for people in rural areas. Complex interventions have not been adapted for remote delivery using mobile health technologies. Strategy training is a complex intervention that teaches clients skills for identifying barriers and solutions to engagement in meaningful activities. Our goal was to adapt the delivery of strategy training for remote delivery using mobile health technology. METHODS: We conducted a sequential descriptive case series study (n=5) in which community-dwelling participants with chronic stroke and prior exposure to strategy training used the iADAPTS mobile health application for 5 weeks. Expert practitioners advised revisions to the intervention process. Safety was assessed via monitoring occurrence of adverse events and risk for adverse events. Acceptability was assessed via the Client Satisfaction Questionnaire-8 (CSQ-8) and the Patient-Provider Connection Short Form of the Healing Encounters and Attitudes Lists (HEAL PPC). RESULTS: Revisions to the intervention process supported the delivery of strategy training using mobile health technology after stroke. No adverse events occurred and risk for adverse events was managed through the intervention process. Acceptability was high (CSQ-8, 25 to 32; HEAL PPC, 59.9 to 72.5). CONCLUSIONS: Strategy training can be adapted for delivery using mobile health technology, with careful consideration to methods for training participants on new technology and the intervention delivery. Future research should establish the efficacy and effectiveness of integrating mobile health in delivery of interventions that promote engagement in client-selected activities and community participation.